Piezoelectric Surgery –A Novel Technique for Laminectomy. (1st April 2015) - Duerr, Felix M.; Seim, Howard B.; Bascuñán, Ana L.; Palmer, Ross H.; Easley, Jeremiah
ABSTRACT Objective: Piezoelectric surgery is a novel technology that allows for the osteotomy of mineralized tissue with less risk of damaging underlying soft tissue structures. This selective cutting increases the safety of osteotomies performed in close vicinity to delicate structures such as dura mater, blood vessels, and neural tissue. This study aimed to develop and describe the technique of piezoelectric surgery for dorsal laminectomy and to assess its clinical safety in normal sheep. Methods: A piezoelectric, dorsal laminectomy technique was developed using ovine cadavers. Following technique development, six live sheep underwent a piezoelectric (n = 6) two-level dorsal laminectomy at L2-L3 and L4-L5 (PiezoL2-3, 4-5), and another 30 live sheep underwent a three-level laminectomy at L1, L3, and L5 (PiezoL1, 3, 5) for a total of 102 laminectomy sites. Surgery time and postoperative complications were recorded. Results: Dorsal laminectomy was safely and accurately performed in 35/36 study sheep using a Piezoelectric surgical instrument. No dural tears were noted in any animal. Non-ambulatory paraparesis in one study sheep (PiezoL1, 3, 5) led to euthanasia at 48 hr and only mild epidural hematoma was noted on necropsy. No other major postoperative complications were observed in any of the animals. Subjectively, PiezoL was easy to perform and with a rapid learning curve. Mean surgery time was 105 min (range: 75–165 min; median: 97.5) for PiezoL2-3, 4-5 and 93 minutes (range 55–100 min; median: 67.5) for PiezoL1, 3, 5. Conclusions: Based on our study, PiezoL is considered a safe and viable technique for performing ovine dorsal laminectomy in the preclinical research setting.